Integrative approaches to psychology and Christianity : an introduction to worldview issues, philosophical foundations, and models of integration - Entwistle, David N. (David Nelson) (2015)
"As disciplines, psychology and theology share an overlapping interest in the nature and functioning of human beings. This book provides an introduction to many of the worldview issues and philosophical foundations that frame the relationship of psychology and theology, includes scholarly reflection on the integration literature, and surveys five paradigms of possible relationships between psychology and Christianity. Questions at the end of each chapter are included to help readers evaluate both the material and their own burgeoning approach to integration. This book is ideal as a textbook for students of psychology and other behavioral and social sciences (social work, sociology, theology, counseling, pastoral counseling) at both the graduate and undergraduate level. It is also written for the broader readership of psychologists, counselors, pastors, and others who are interested in integration" -- Publisher description.
Introduction: the fork in the road -- The question of necessity: Athens and Jerusalem -- Allies or enemies? Historical views on faith and science -- The soul of psychology and the psyche of the soul -- Windows on the world: assumptions and worldviews -- The pursuit of truth: epistemology, ways of knowing -- The nature of the world: metaphysics -- The nature of humanity: philosophical anthropology -- Understanding and making models -- Antagonistic models of disciplinary relationship: enemies -- Intermediate models of disciplinary relationship: spies, colonialists, rebuilders, and neutral parties -- Integrative models of disciplinary relationship: allies -- Integration in research and practice -- Discerning your place in the integration story.
Includes bibliographical references (pages 335-354) and indexes.
Keywords: Christianity -- Psychology; Psychology and religion; Christian philosophy; Christian philosophy; Christianity -- Psychology; Psychology and religion